Synthesis and Electrochemical Study of CoNi2S4 as a Novel Cathode Material in a Primary Li Thermal Battery. Issue 9 (1st January 2017) - Giagloglou, Kyriakos; Payne, Julia L.; Crouch, Christina; Gover, Richard K. B.; Connor, Paul A.; Irvine, John T. S.
Abstract : In this work CoNi2 S4 was investigated as a candidate cathode material for Li thermal batteries. The CoNi2 S4 was synthesized by a solid state reaction at 550°C in a sealed quartz tube. Neutron powder diffraction was utilized to confirm normal spinel structure up to 200°C, however, there was cation disorder above this temperature. The electrochemical properties of the batteries were investigated at 500°C by galvanostatic discharge to elucidate the mechanism and the products NiS, Co3 S4 and Co9 S8 of the discharge mechanism were confirmed using powder X-ray diffraction. CoNi2 S4 exhibits two voltage plateaus vs Li13 Si4 at 500°C, one at 1.75 V and the second at 1.50 V. CoNi2 S4 has an overall capacity of 318 mA h g −1 from OCV 2.58 V to 1.25 V vs Li13 Si4 which is comparable to that of the well-known metal disulfides.